A Design of a Redundancy-Based Cascaded Bidirectional DC–DC Converter for Improved Reliability in Energy Storage Devices - Thales Augusto Fagundes; Guilherme Henrique Favaro Fuzato; Rafael Fernando Quirino Magossi; Ana Lais Rui Oliveira; Ricardo Quadros Machado (IEEE Open Journal of the Industrial Electronics Society)
This article proposes a redundancy-based cascaded bidirectional dc/dc converter designed to interface battery energy storage system (BESS) units. With the employment of this topology, its reliability is increased due to redundancy in power conversion, which differs from conventional structures formed by dc/dc converters that cannot process power flow when a fault occurs. Thus, the topology is provided merging the cascaded bidirectional Boost converter and cascaded bidirectional Cuk converter. Subsequently, the coupled mathematical model of the proposed topology can be readily calculated, considering all feasible (different) subcircuits according to the switching pattern. Therefore, small-signal analysis is applied to design the PI controllers, followed by a closed-loop performance evaluation using an infinity norm and stability analysis to assess the operation of the dc/dc converter in closed loop for different values of load and current references. Finally, a lab-scale prototype and a hardware-in-the-loop setup prove the effectiveness of the dc/dc converter working in various scenarios and also operating with the traditional SoC-based droop for balancing the BESS units.